The interpersonal communication as a way to promote women's incorporation to the recreational activities - Daisy Leyva-Fonseca (Universidad de Guantánamo, 2014)
The present paper offers communicative actions to promote a greater incorporation of women of average age to recreational activities. All participants are liable, and the proposal implicates the members of the team of facilitators (the family's doctor, the professor of recreation, the social worker). Different communicative activities are to take effect in order to achieve the objective of the proposal, designed to act on individual and group parameters and to make easy the communicative relations among women. Methods of different levels allowed verifying the insufficiencies detected, and at the same time the communication between women as a group of the community improved.